Globalization and its impact on public policy formulation and implementation: case study of forest conservation in Sabah - Haijon Gunggut (2009)
This focus of this thesis is to study how the process of globalization affected forest use and policy development in Sabah using historical and survey methods. Recognizing the multiple effects of globalization process, it is argued that globalization has resulted in not only severe loss and degradation of the forests but also contributed to the conservation of forests. On the one hand, forces under economic globalization, namely development practice, increasing global demand of tropical woods, consumerism ideology and emphasis on competition, contributed to the rampant forest exploitation. Furthermore, economic globalization facilitated the exploitation of forests through local sociopolitical dynamics such as patronage, federal-state politics and wealth seeking behavior thus accelerating forest loss and degradation. On the other hand, globalization played significant role in the acceptance of forest conservation agenda by the state. The globalization of the idea that forests' survival was crucial for the maintenance of the ecosystem fueled forest conservation effort. In addition, economic globalization contributed to sustainable exploitation of the forests within the context of sustainable development framework. International bodies including NGOs such WWF, collaborated with local institutional actors to boost the acceptance of forest conservation as a major state agenda. The implementation of forest conservation agenda reflects both market and conservation needs under globalization. The state's commitment to conservation was reflected by the various legislations related to forest conservation since the mid 1990s, but actual implementation suggests emphasis on financial gains. Furthermore, conservation efforts did not result in better condition of the forests although the size of forest conservation area had significantly increased.